Psychiatric Nursing in Iraq: Past, Present, and Promising Futures - Abdulqadir, Salar; Ahmed, Sirwan; Muhammad, Omar (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2024)
This review discusses the current state of psychiatric nursing in Iraq and emphasizes the need for improvement. It explores the historical background of psychiatric nursing in Iraq, including its evolution and the impact of socio-political factors. Psychiatric nursing in Iraq faces a number of difficulties, including a shortage of qualified nurses, stigma surrounding mental health, a lack of services, limited infrastructure, and a lack of established protocols. The various strategies to shape the future of psychiatric nursing in Iraq are urgently needed. These include training and recruitment programs to address the shortage of nursing personnel, awareness campaigns and policy advocacy to reduce societal prejudice, the use of technology and community-centred care models to improve access to mental health services, the establishment of infrastructure and resources, and the implementation of standardized practices. The role of government policies in shaping psychiatric nursing is also discussed. The paper critically analyses the impact of policies, calls for increased government support and resource allocation, and explores international cooperation and best practices. Ethical considerations in psychiatric nursing are also examined, including the protection of patient rights, the preservation of human dignity, and the development of cultural competency. In conclusion, this review highlights the challenges and opportunities for psychiatric nursing in Iraq and emphasizes the importance of ongoing efforts and financial commitment. It calls on individuals and organizations involved in mental health and nursing to actively participate in promoting the progress of psychiatric nursing in Iraq.